Simultaneous Electrochemical Determination of Chlorzoxazone and Diclofenac on an Efficient Modified Glassy Carbon Electrode by Lanthanum Oxide@ Copper(I) Sulfide Composite - Baniahmad, Bahar; Hassani Nadiki, Hadi; Jahani, Shohreh; Nezamabadi-Pour, Najmeh; Toolabi, Ali; Foroughi, Mohammad Mehdi (Frontiers in Chemistry, 2022)
This study synthesized a La2O3@snowflake-like Cu2S composite to fabricate electrochemical sensor for sensitively simultaneous detection of diclofenac and chlorzoxazone exploiting an easy hydrothermal approach, followed by analyzing with XRD, FE-SEM and EDX methods. According to voltammetric studies, the electrocatalytic diclofenac and chlorzoxazone oxidations on the electrode modified with La2O3@SF-L Cu2S composites were increased, with greater oxidation currents, as well as the oxidation potential was significantly decreased due to synergetic impact of La2O3 @SF-L Cu2S composites when comparing with the pure SF-L Cu2S NS-modified electrode. The DPV findings showed wide straight lines (0.01 to 900.0 μM) for La2O3 NP@SF-L Cu2S NS-modified electrode with a limit of detection (LOD) of 1.7 nM and 2.3 nM for detection of diclofenac and chlorzoxazone, respectively. In addition, limit of quantification (LOQ) were calculated to be 5.7 nM and 7.6 nM for diclofenac and chlorzoxazone, respectively. The diffusion coefficient was calculated to be 1.16×10−5and 8.4×10−6 cm2/s for the diclofenac and chlorzoxazone oxidation on the modified electrode, respectively. Our proposed electrode was examined for applicability by detecting diclofenac and chlorzoxazone in real specimens.